2021
DOI: 10.1159/000517427
|View full text |Cite
|
Sign up to set email alerts
|

Does the Timing of Radiosurgery after Grade 1 Meningioma Resection Affect Long-Term Outcomes?

Abstract: <b><i>Background:</i></b> Meningiomas are the most common benign intracranial tumors. Gamma Knife® stereotactic radiosurgery (GKSRS) has become a preferred management for recurrent or residual meningiomas. This study focuses on the relationship between tumor control and the time interval between resection of a World Health Organization (WHO) grade 1 meningioma and GKSRS. <b><i>Methods:</i></b> This single institution retrospective analysis reviewed our experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Early surveillance and identification of intracranial disease, as well as The association between outcomes after SRS and the type of primary disease continues to be an area of focused research. Bowden et al 12 found that patients with breast cancer had median survival of 16 months, while those with lung cancer and melanoma had a median survival of 4.6 and 3.1 months, respectively. In patients treated with multiple sessions of SRS for a cumulative number of ≥25 metastases, Benjamin et al 3 reported similar differences survival by the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Early surveillance and identification of intracranial disease, as well as The association between outcomes after SRS and the type of primary disease continues to be an area of focused research. Bowden et al 12 found that patients with breast cancer had median survival of 16 months, while those with lung cancer and melanoma had a median survival of 4.6 and 3.1 months, respectively. In patients treated with multiple sessions of SRS for a cumulative number of ≥25 metastases, Benjamin et al 3 reported similar differences survival by the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Two strategies are usually proposed: an early treatment of the residue or an initial wait-and-see approach with serial MRI follow-ups with secondary treatment (in this case RRS) reserved only when recurrence is observed. Some studies support the role of an early postoperative radiosurgical treatment in improving PFS compared to a treatment at recurrence (11,(43)(44)(45). Frostell et al (46) published a study in which they confronted adjuvant radiosurgical treatment after subtotal resection of meningiomas involving the SSS.…”
Section: Timing Of Rrsmentioning
confidence: 99%
“…The details of Gamma Knife SRS procedures have been documented in previous publications. 7 To summarize, a Leksell stereotactic head frame was attached to the patient's head using mild conscious intravenous sedation and local anesthetic to help with skull pin placement. A high-resolution T1-weighted contrast-enhanced axial brain MRI (1.5 mm slice) was performed.…”
Section: Stereotactic Radiosurgery Techniquementioning
confidence: 99%
“…Previously reported studies have helped to clarify the role of SRS in patients with meningiomas. 7,18 Recently, radiosurgery emerged as a treatment option for orbital meningiomas and ONSMs. In a retrospective study of 7 patients with orbital meningioma who underwent Gamma Knife SRS, Kim et al 19 reported that local tumor control was achieved in 6 of 7 patients over the follow-up period of 7-50 months.…”
Section: The Role Of Stereotactic Radiosurgery As An Adjuvant Therapymentioning
confidence: 99%